Case-fatality and sequelae following acute bacterial meningitis in South Africa, 2016 through 2020. (September 2022) - Meiring, Susan; Cohen, Cheryl; de Gouveia, Linda; Plessis, Mignon du; Quan, Vanessa; Kleynhans, Jackie; Menezes, Colin; Reubenson, Gary; Dawood, Halima; Nchabeleng, Maphoshane; Said, Mohamed; Mvelase, Nomonde; et al.
Highlights: Despite available vaccines and antibiotics, bacterial meningitis is deadly. In South Africa, a middle-income country, over one in three individuals with bacterial meningitis die. A total of 24% of survivors reported sequelae, and 5% died within 2 months of hospital discharge. HIV (particularly in individuals with low cluster of differentiation [CD4] T cell counts) was a risk factor for death. Abstract: Objectives: Providing country-specific estimates of case fatality and sequelae from bacterial meningitis (BM) is important to evaluate and monitor progress toward the World Health Organization's roadmap to "defeating meningitis by 2030". Methods: From 2016-2020, GERMS-SA conducted enhanced surveillance at 26 hospitals across South Africa. Episodes of laboratory-confirmed BM due to Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis were included. Risk factors for in-hospital death and sequelae at hospital discharge among survivors were analyzed. Results: Of 12, 717 invasive bacterial infections reported nationally, 39% (4980) were from enhanced surveillance sites, including 4159 pneumococcal, 640 H. influenzae, and 181 meningococcal infections. BM accounted for 32% (1319/4159) of pneumococcal, 21% (136/640) of H. influenzae, and 83% (151/181) of meningococcal invasive diseases. Clinical data were available for 91% (1455/1606) of BM: 26% (376/1455) were aged <5 years, 50% (726/1455) were female, and 62% (723/1171) with known HIV results, were HIV-infected. In-hospital case fatality was 37% (534/1455), and 24% (222/921) of survivors had adverse sequelae. Risk factors for death included altered mental status, HIV infection, and comorbidities. Risk factors for adverse sequelae included altered mental status and antimicrobial nonsusceptibility. Conclusion: BM in South Africa has a high case fatality, and adverse sequelae frequently occur among survivors. Those with comorbidities (including HIV) are at the highest risk. Graphical abstract: Image, graphical abstract